Scientific Opinion on application EFSA‐GMO‐BE‐2013‐117 for authorisation of genetically modified maize MON 87427 × MON 89034 × NK603 and subcombinations independently of their origin, for food and feed uses, import and processing submitted under Regulation (EC) No 1829/2003 by Monsanto Company. (1st August 2017) - ,; Naegeli, Hanspeter; Birch, Andrew Nicholas; Casacuberta, Josep; De Schrijver, Adinda; Gralak, Mikołaj Antoni; Guerche, Philippe; Jones, Huw; Manachini, Barbara; Messéan, Antoine; Nielsen, Elsa Ebbesen; Nogué, Fabien; et al.
Abstract: In this opinion, the EFSA Panel on Genetically Modified Organisms (GMO Panel) assessed the three‐event stack maize MON 87427 × MON 89034 × NK603 and its three subcombinations, independently of their origin. The GMO Panel has previously assessed the three single events combined to produce this three‐event stack maize and did not identify safety concerns. No new data on the single events, leading to modification of the original conclusions on their safety, were identified. Based on the molecular, agronomic, phenotypic and compositional characteristics, the combination of the single maize events and of the newly expressed proteins in the three‐event stack maize did not give rise to issues regarding food and feed safety or nutrition. In the case of accidental release of viable grains of maize MON 87427 × MON 89034 × NK603 into the environment, the three‐event stack maize would not raise environmental safety concerns. The GMO Panel concludes that the three‐event stack maize is as safe and as nutritious as the non‐GM comparator and the tested non‐GM reference varieties in the context of its scope. The GMO Panel considered that its previous conclusions on the two‐event stack maize MON 89034 × NK603 remain valid. For the two maize subcombinations for which no experimental data were provided the GMO Panel assessed the likelihood of interactions among the single events, and concluded that their combination would not raise safety concerns. These two subcombinations are therefore expected to be as safe as the single events, the previously assessed maize MON 89034 × NK603 and maize MON 87427 × MON 89034 × NK603. Since the post‐market environmental monitoring plan for the three‐event stack maize does not include any provisions for the two subcombinations not previously assessed, the GMO Panel recommended the applicant to revise the plan accordingly.